STUDIES ON FOOD AND FEEDING HABITS OF CATFISH TACHYSURUS TENUISPINIS (DAY) - Mojumder, P; Dan, S S (Indian Journal of Fisheries, 2011)
It is observed that 37% of the food of Tachysurus teniiispinis, consists ofcrabs, prawns, Squilla sp and orustacesn remains; 26% polychaetes, 6.5%molluscs, 6.3% teleosts, 4.2% ophiuroids and the rest miscellaneous food items.T. tenuispinis is, therefore, a carrtivorous bottom feeder. As a single food item,polychaetes are most preferred.The fTuctuations in the intensity of feeding (points) and the volume ofstomach contents (ml) in different months generally showed similar trends bothin the small (less than 27.5 cm total length) and large (more than 27.5 cm totallength) catfish. The relative importance of various food items during differentmonths shows that feeding is selective